STRATEGI PEMASARAN "LUXURY TOURISM" DI BALI NATIONAL GOLF VILLAS, NUSA DUA BALI (Jurnal Destinasi Pariwisata, 2026)
This study examines the marketing strategies applied in the Luxury Tourism segment by Bali National Golf Villas, located in Nusa Dua, Bali. Luxury Tourism refers to premium travel experiences that emphasize exclusivity, comfort, privacy, and personalized services designed to meet the expectations of high-end tourists. The purpose of this study is to analyze the marketing strategies implemented by Bali National Golf Villas and to examine how the Luxury Tourism concept is integrated into its overall business operations. This research employs a qualitative method with a descriptive approach, with data collected through in-depth interviews, direct observations, and literature studies to obtain a comprehensive understanding of the strategies applied. The findings indicate that the marketing strategies focus on creating exclusive and personalized guest experiences supported by luxury facilities, high service quality, and strong brand positioning. In addition, digital marketing plays a significant role in promoting the property by enhancing brand visibility and reaching targeted luxury market segments through online platforms. The implementation of these strategies contributes to strengthening the competitive advantage of Bali National Golf Villas and reinforces its position within the luxury tourism market in Bali.